Factors influencing aggressiveness of Botryosphaeriaceae species in Nopalea cochenillifera - Conforto, Erica Cinthia (2023)
Nopalea cochenillifera is an important source of animal feed in the semi-arid region of northeastern Brazil, but it is affected by cladode brown spot (CBS) caused by Botryosphaeriaceae species. This study investigated the effects of wounding, temperature, and wetness on the aggressiveness of four species of Botryosphaeriaceae associated with CBS: Lasiodiplodia iraniensis, L. pseudotheobromae, L. theobromae, and Neofusicoccum batangarum. No species induced symptoms in unwounded cladodes, whereas all species induced symptoms in wounded cladodes. All species expressed the highest aggressiveness when inoculated immediately after wounding, with aggressiveness decreasing with increasing wound age. Neofusicoccum batangarum was the most sensitive species to wound age. All Botryosphaeriaceae species induced symptoms in cladodes at 10 °C, and only L. pseudotheobromae did not induce symptoms at 40 °C. The species differed in their optimal temperatures for maximum aggressiveness, which varied between 22.2 ºC (L. pseudotheobromae) and 30.4 ºC (L. theobromae). All species induced symptoms in the absence of wetness, and the optimal wetness duration ranged from 12.7 h (N. batangarum) to 16.0 h (L. theobromae). The species differed in levels of aggressiveness under all conditions tested. In most experiments, L. iraniensis was the most aggressive species.